Tax Smoothing with Financial Instruments - Bohn, Henning (American Economic Review, 1990)
The paper analyzes the optimal structure of government debt in a stochastic environment. In a model with distortionary taxes, the government should smooth tax rates over states of nature as well as over time. Government liabilities should be structured to hedge against macroeconomic shocks that affect the government budget. The optimal structure of government liabilities generally includes some "risky" securities which are state-contingent in real terms. The empirical part of the paper tests for tax smoothing and then studies state contingencies implemented by some specific securities including nominal debt, long-term bonds, equity, and foreign-currency debt.